2006
DOI: 10.1016/j.rapm.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mepivacaine Versus Lidocaine for Episcleral (Sub-Tenon’s) Block for Cataract Surgery in an Ambulatory Setting

Abstract: We found no argument to favor lidocaine over mepivacaine in episcleral (sub-Tenon's) eye block, especially in terms of motor-block duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Also, mepivacaine group did not experience more pain. 2 Borel et al also recommended using mepivacaine and lidocaine rather than bupivacaine in day case cataract surgeries due to good block and short duration. 26 Fanelli 19 The shorter duration of the block with mepivacaine was likewise expected from its pharmacology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, mepivacaine group did not experience more pain. 2 Borel et al also recommended using mepivacaine and lidocaine rather than bupivacaine in day case cataract surgeries due to good block and short duration. 26 Fanelli 19 The shorter duration of the block with mepivacaine was likewise expected from its pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…Ripart et al found no favor with lidocaine over mepivacaine in episcleral (sub-Tenon's) eye block, especially in terms of motor-block duration. 2 Neuromuscular blocking drugs, such as atracurium 27 and vecuronium, 28 have also been added to the local anesthetic mixtures and have been shown to enhance the quality of PBA…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation